Implementasi Nilai-Nilai Pendidikan Islam Multikultural pada Pendidikan Dasar - Arif Muzayin Shofwan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
The implementation of multicultural Islamic educational values ​​is essential in basic education (primary schools and Islamic elementary schools) in Indonesia, which has diverse religions, ethnicities, cultures, customs, and the like. The implementation of multicultural Islamic educational values ​​in basic education is believed to be able to shape students into individuals with multicultural character who are able to respect and appreciate all diversity. This paper aims to examine the implementation of multicultural Islamic educational values ​​in basic education. This research utilized a literature review in data collection. The data analysis technique used content analysis by sorting the data according to the research objectives. The findings of this paper are that the implementation of multicultural Islamic educational values ​​in basic education can be carried out by considering the following factors: (1) the principles of multicultural education and Islamic religious education; (2) the emphasis on multicultural values ​​in Islamic religious education; and (3) the important role of Islamic religious education teachers and educational institutions. Implementing these multicultural Islamic educational values ​​is believed to be a means of building a more substantive, contextual, positive, and socially active civilization in Indonesia's diverse nation.